The Dominance of Liking: Uncovering Dyadic and Reputational Effects of Peer and Perceived Teacher Likes and Dislikes on Friendship Dynamics Among Chinese Adolescents - Qin, Xingna; Laninga-Wijnen, Lydia; Steglich, Christian; Zhang, Yunyun; Ren, Ping; Veenstra, René (Springer Science and Business Media LLC, 2025)
While previous research suggests that peer and teacher preferences are linked to adolescents' peer relationships, the specific impact of peer and teacher (dis)liking on adolescents' friendship networks is not fully understood. This study used longitudinal social network analysis to examine how peer (dis)liking and perceptions of teacher (dis)liking predicted friendship selection among Chinese adolescents. Questionnaires were administered to a sample of 2566 students (48.3% boys, Mage = 13.94, SDage = 0.60 at Time 1) in central China in 2015 and 2016. Results for peer (dis)liking revealed that Chinese students tended to befriend peers they liked (dyadic perception), to befriend peers widely liked (reputational perception), and to avoid peers widely disliked (reputational perception). Regarding teacher (dis)liking, Chinese students tended to befriend peers they believed their teachers liked (dyadic perception) and avoid those widely perceived as liked by teachers (reputational perception). Interestingly, students who were widely perceived as liked by teachers tended to befriend peers whom they believed teachers disliked. Perceived teacher disliking had a limited effect on friendship selection at both the dyadic and reputational levels. These findings suggest that peer liking and perceived teacher liking relate to friendship formation among Chinese adolescents, but that a reputation as a teachers' pet may hinder their friendships.